Compositionally Disordered Doped with Cerium Crystalline Garnet Type Materials for Brighter and Faster Scintillations - M. V. Korzhik (Приборы и методы измерений, 2021)
Ce-doped tetracationic garnets (Gd, M)3Al2Ga3O12(M = Y, Lu) form a family of new multipurpose promising scintillation materials. The aim of this work was to evaluate the scintillation yield in the materials of quaternary garnets activated by cerium ions with partial isovalent substitution of the matrix-forming gadolinium ions by yttrium or lutetium ions.Materials were obtained in the form of polycrystalline ceramic samples, and the best results were shown by samples obtained from the raw materials produced by the coprecipitation method. It was found that ceramics obtained from coprecipitated raw materials ensure a uniform distribution of activator ions in the multi-cationic matrices, which enables the high light yield and fast scintillation kinetics of the scintillation. It was demonstrated that the superstoichiometric content of lutetium/gadolinium in the material is an effective method to suppress phosphorescence accompanied scintillation. For ceramics with the composition (Gd, Lu)3Al2Ga3O12 , a scintillation yield of more than 50.000 ph/MeV was achieved. The scintillation kinetics was measured to be close to the kinetics with a decay constant of 50 ns.In terms of the set of the parameters, the developed scintillation materials are close to the recently developed alkali halide materials LaBr3:Ce, GdBr3:Ce. Moreover, they have high mechanical hardness, are characterized by the absence of hygroscopicity, and are better adapted to the manufacture of pixel detectors used in modern devices for medical diagnostics.